'That's just how medicine is': A remote ethnographic study of Ireland's failure to meet the core work needs of its hospital doctors - Niamh Humphries; Jennifer Creese; Aoife M. McDermott; Gabrielle Colleran; Cian McDermott; John-Paul Byrne (Elsevier, 2024)
This study focuses on hospital doctors' experiences of work during the pandemic. The context is the Irish health system, under considerable strain due to the pandemic and a legacy of austerity/under-funding. Although medicine is considered a prestigious job, hospital doctors often endure challenging working conditions and work-life imbalance. In this paper we consider how a narrative of 'medicine-as-vocation' is used to excuse challenging working conditions and to impede change. West and Coia (2019) proposed a set of core work needs required to support doctor wellbeing and minimise work-related stress, i.e. autonomy/control, belonging and competence and these are applied as a lens to examine the everyday work experiences of respondent hospital doctors. Data collection was conducted in 2021 using a remote ethnographic method - Mobile Instant Messaging Ethnography (MIME) - developed by the research team to enable data collection at a time of pandemic restrictions (Humphries, Byrne, et al, 2022). Twenty-eight hospital doctors were recruited for the study. Each respondent was interviewed twice and engaged in a 12-week conversation with the research team via WhatsApp. We report hospital doctors' experiences of heavy workloads, weak line management and the challenges of influencing change at work. Overall, the findings presented demonstrate the myriad ways that Ireland is failing to meet the core work needs of its hospital doctors and how 'medicine-as-vocation' is used to justify organisational neglect.